Virtual Influencers vs. Human Influencers in the Age of Digital Transformation: Which Holds Greater Influence? (Mutah Journal of Humanities and Social Sciences (MJHSS), 2025)
The popularity of influencer marketing seems to be on the rise lately, particularly within the tourism sector, where it is being increasingly utilized with significant space for expansion. A novel aspect of this marketing strategy that remains relatively under the radar is virtual influencers (VIs). This study delved into the comparative effectiveness of human (HIs) versus VIs, a topic that has yet to be explored extensively. The results of this study revealed that both influencers (HIs and VIs) have a strong and positive impact on perceived trustworthiness (PT), customers' booking intention (CBI), perceived usefulness (PU), and social presence (SP). Moreover, the study highlighted the crucial role of PT, indicating a positive influence on CBI. PU was also shown to boost CBI significantly. However, the direct impact of SP on booking intentions did not present a statistically significant result. This study contributes significantly to the influencer marketing domain, offering promising insights and laying the groundwork for further exploration. Both theoretical and practical implications of these findings are discussed.
Keywords: Human Influencers (HIs); Virtual Influencers (VIs); Perceived Trustworthiness (PT).; Perceived Usefulness (PU); Social Presence (SP),; Customers Booking Intention (CBI)